Worker or shirker: Who evades more taxes?. A real effort experiment - Christoph Bühren; Thorben Kundt (Philipps-University Marburg, Faculty of Business Administration and Economics, 2013)
With the help of a real effort experiment, we analyze if tax evasion depends on the amount of effort invested to generate income. In three treatments, subjects were either endowed with income or had to work moderately or hard to earn it. In line with prospect theory, subjects evaded more taxes when they worked hard for their income. We find little evidence for the prediction that tax evasion in the endowed treatment is higher than in the moderate work treatment.
Keywords: C91; D03; H26; 330; tax evasion; prospect theory; house money effect; sunk cost effect; real effort experiment